2021
DOI: 10.1021/acs.nanolett.1c02728
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Low Abundance Genes of Single Point Mutation

Abstract: Cell-free DNA (cfDNA) analysis, specifically circulating tumor DNA (ctDNA) analysis, provides enormous opportunities for noninvasive early assessment of cancers. To date, PCR-based methods have led this field. However, the limited sensitivity/specificity of PCR-based methods necessitates the search for new methods. Here, we describe a direct approach to detect KRAS G12D mutated genes in clinical ctDNA samples with the utmost LOD and sensitivity/specificity. In this study, MutS protein was immobilized on the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Very recently, a direct SMFS-based approach to identify the KRAS G12D mutation in the circulating tumor DNA (ctDNA) samples that are extracted from patients’ plasma with very low mutant allele frequencies (0.006–0.2%) at high sensitivity and specificity (near 100%) has been reported. 4 In this work, a LNA/DNA chimeric blocker has been added into the ctDNA sample before the denaturation step to make the desired target sequence available to the capture probe. Applicability of this assay for EGFR mutated DNA in cell-free DNA (cfDNA) samples was also assessed.…”
Section: The Xnas As Troubleshootermentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a direct SMFS-based approach to identify the KRAS G12D mutation in the circulating tumor DNA (ctDNA) samples that are extracted from patients’ plasma with very low mutant allele frequencies (0.006–0.2%) at high sensitivity and specificity (near 100%) has been reported. 4 In this work, a LNA/DNA chimeric blocker has been added into the ctDNA sample before the denaturation step to make the desired target sequence available to the capture probe. Applicability of this assay for EGFR mutated DNA in cell-free DNA (cfDNA) samples was also assessed.…”
Section: The Xnas As Troubleshootermentioning
confidence: 99%
“…Therefore, sequence-specific and sensitive detection of nucleic acids is vital for early and reliable diagnosis of a genetic disease. The identification of certain nucleic acid sequences both in vitro and in vivo is important also for the discovery of hitherto unknown genetic diseases, diagnosis of pathogen infection and monitoring of disease treatment. , The nucleic acid biosensors (NABs) or the genosensors, where detection is based on nucleic acid hybridization, have shown considerable potential, especially for clinical analysis, for example, in the cases of metabolic disorders like diabetes, cancer and cardiovascular disease; contagious diseases like tuberculosis, dengue and hepatitis; and food borne diseases like diarrhea, salmonellosis, cholera etc. , …”
Section: Introductionmentioning
confidence: 99%
“…Circulating tumor DNA (ctDNA), consisting of small nucleic acid fragments released by tumor cells into the peripheral blood, carries comprehensive tumor data, thus serving as an informative molecular biomarker for cancer diagnosis. , Analysis of ctDNA has propelled extensive research in developing minimally invasive liquid biopsies for the assessment of various diseases. , To date, considerable progress has been made in identifying ctDNAs linked to cancer onset and progression, thereby facilitating customized medication strategies. For example, researchers have demonstrated that patients with CRC bearing mutations in codons 12 or 13 of the KRAS gene (one of the most frequently mutated ctDNAs in CRC, accounting for 30–60% of all cases) should not receive antiepidermal growth factor receptor (anti-EGFR) monoclonal antibody (cetuximab or panitumumab) therapy. Consequently, KRAS mutation analysis has become the standard procedure for diagnosing and treating patients with metastatic CRC. , However, trace amounts of ctDNA in serum (typically in the pico-to-femtomolar concentration range) and the presence of interference from wild-type and other homologous species render the identification of KRAS mutations challenging in clinical samples …”
Section: Introductionmentioning
confidence: 99%
“…22−24 Research has even immobilized the MutS at the tip of an atomic force microscope to detect mismatches within double-stranded structures formed by mutant DNA, constructing a highly sensitive and specific mutation detection approach with sensitivity down to 0.006%. 25 Evrony et al introduced a novel MutS-based biosensor. They integrated bacterial MutS with a fiber-optic plasmon resonance sensing system for gene mutation detection, achieving a sensitivity of 1%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, gene mutation detection methods based on MutS have garnered significant attention. The underlying principle involves the inhibition of DNA polymerase strand–displacement activity upon MutS binding to mismatched DNA, thereby preventing the connection of DNA duplexes and impeding PCR amplification. Research has even immobilized the MutS at the tip of an atomic force microscope to detect mismatches within double-stranded structures formed by mutant DNA, constructing a highly sensitive and specific mutation detection approach with sensitivity down to 0.006% . Evrony et al introduced a novel MutS-based biosensor.…”
Section: Introductionmentioning
confidence: 99%